2013
DOI: 10.1155/2013/693613
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hepatoprotective Effect of Aqueous Extract of Germinated and Fermented Mung Bean on Ethanol-Mediated Liver Damage

Abstract: Mung bean is a hepatoprotective agent in dietary supplements. Fermentation and germination processes are well recognized to enhance the nutritional values especially the concentration of active compounds such as amino acids and GABA of various foods. In this study, antioxidant and hepatoprotective effects of freeze-dried mung bean and amino-acid- and GABA-enriched germinated and fermented mung bean aqueous extracts were compared. Liver superoxide dismutase (SOD), malondialdehyde (MDA), ferric reducing antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 46 publications
3
36
1
Order By: Relevance
“…Similarly, these herbs are also protective in animal models of radiation injury [128] and chemical toxemia [129], although it is not yet known whether the protective mechanism is dependent on the HMGB1 suppression. In addition, an increasing number of herbal components (e.g., nicotine, EGCG, tanshinone, glycyrrhizin, chlorogenic acid, Emodin-6-O-β-D-glucoside, Rosmarinic acid, isorhamnetin-3-O-galactoside, Persicarin, Forsythoside B, chloroquine, acteroside) [103,130-140] have been proven effective in inhibiting endotoxin-induced HMGB1 release ( Figure 3, Table 2 ).…”
Section: Therapeutic Potential Of Hmgb1-inhibiting Agentsmentioning
confidence: 99%
“…Similarly, these herbs are also protective in animal models of radiation injury [128] and chemical toxemia [129], although it is not yet known whether the protective mechanism is dependent on the HMGB1 suppression. In addition, an increasing number of herbal components (e.g., nicotine, EGCG, tanshinone, glycyrrhizin, chlorogenic acid, Emodin-6-O-β-D-glucoside, Rosmarinic acid, isorhamnetin-3-O-galactoside, Persicarin, Forsythoside B, chloroquine, acteroside) [103,130-140] have been proven effective in inhibiting endotoxin-induced HMGB1 release ( Figure 3, Table 2 ).…”
Section: Therapeutic Potential Of Hmgb1-inhibiting Agentsmentioning
confidence: 99%
“…For example, soy protein and isoflavones have been approved by the US Food and Drug Administration to be used as health foods for control of triglyceride (TG) and total cholesterol levels [4]. Mung bean ( Vigna radiata ) is a legume that contains large amounts of protein, essential amino acids, and metabolites such as γ -amino butyric acid (GABA) [5]. In Chinese medicine, mung bean has been widely used to prepare mung bean soup for cooling and detoxification of the body [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese medicine, mung bean has been widely used to prepare mung bean soup for cooling and detoxification of the body [6]. Moreover, mung bean was found to be a potent antioxidant and hepatoprotective agent [5]. Our earlier research has reported the potential of fermentation in improving these effects shown by the mung bean [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term consumption of excess alcohol can lead to liver injury [18]. The activities of serum ALT and AST are liver injury biomarkers, and their significant elevations denote increased permeability and injury, necrosis of hepatocytes, or a combination of the above [19].…”
Section: Resultsmentioning
confidence: 99%